The legal position of community mediation in Khyber Pakhtunkhwa: a critical analysis - Ahmad, Muhamad Hassan; Khan, Ihtesham Ullah; Eishan Jan, Mohammad Naqib; Md. Dahlan, Nuarrual Hilal (Serials Publications (P) Ltd., 2019)
Resolving neighbourhood disputes in the community through amicable settlements has been in practice in different provinces of Pakistan in various forms such as Panchayat, Jirga, Faislo. Nevertheless, these traditional dispute settlement mechanisms do not exactly resemble the contemporary community mediation practices. Accordingly, this paper aims to discover the legal status of community mediation in the Pakistani legal system. It can be observed that there is no specific legal framework governing the community mediation, the training and qualifications of community mediators, and the community mediation centres in Khyber Pakhtunkhwa. Thus, this paper proposes that there is a need to legislate a comprehensive legal framework which covers mediation from all dimensions - including community mediation - at the federal level by giving importance to the traditional dispute resolution methods in place in various provinces of Pakistan and also learning experiences from other suitable jurisdictions.